(untitled) (Bangladesh Medical Journal, 2022)
Vitamin D deficiency has emerged as a concerning public health issue, and almost 25-50% of patients with proximal muscle weakness suffer for this deficiency. It has been documented that myopathy could be a presentation of hypovitaminosis D. Most often, it remains unnoticed or undiagnosed because muscle weakness develops gradually over the years. As fewer studies are available on this topic, the study was designed to assess the vitamin D status in patients presenting with proximal muscle weakness. This hospital-based descriptive cross-sectional study was conducted at the Inpatient and outpatient Department of Medicine of Dhaka Medical College Hospital for 6 months following approval of this protocol. The Ethical Review Committee approved the protocol, and informed written consent was obtained from all the patients. The patients were selected as per inclusion and exclusion criteria with the purposive sampling method. Data were collected by a preformed semi-structured questionnaire. Total 50 patients were included in the final analysis. Collected data were analyzed by the Statistical Package for the Social Sciences version-22 (SPSS). Among 50 patients, 70% were females and mean age was 58.92 ± 12.3 years with a frequent age group> 65 years (46%), where more than two third (68%) of the respondents were from urban area. Among the study subjects, the majority of them had involvement of the lower limb muscles (54%) and one-fifth of them (20%) had both upper and lower limb involvement, whereas more than one-fourth (26%) had only upper limb involvement. The mean duration of illness was 8. 6 ± 3.4 months. The study found more than three fourth, (78%) had hypovitaminosis D the and mean value of serum 25(0H) D was 22.3 ± 7.7 ng/ml. Among them 36% had mild insufficiency, 30% had a moderate deficiency, and 12% had severe deficiency. About two-thirds of proximal myopathy patients had hypovitaminosis D. Difficulties in walking, standing from sitting, climbing, raising hands above the head, bone and joint pain were significantly associated with the severity of vitamin D deficiency (P-value < 0.05). The severity of muscle weakness was strongly associated with the severity of vitamin D deficiency (P-value <0.05). Females were comparatively more affected than males, it was not statistically significant. However, further large-scale analytical studies are needed to find the association of this hypovitaminosis with the disease process. Bangladesh Med J. 2021 Sept; 50(3): 7-13